Análise numérica de pilares mistos preenchidos com concreto reciclado sob compressão axial centrada - Oliveira, Tawan Mundim de (2023)
Part of the waste generated in civil construction, especially waste concrete, can be used as replacement of natural aggregates. Aiming to expand the use of concrete with recycled aggregates in composite columns, the aim of this study was to evaluate the behavior of composite columns filled with recycled concrete subjected to concentric load. For this, numerical simulation was developed in software Abaqus. First, a systematic review of the literature (SRL) on circular cross-section composite columns filled with recycled concrete was conducted. Most of the available studies are related to experimental results showing an increase in ultimate load due to the use of recycled concrete. Numerical models were developed in software Abaqus® and a sensitivity analysis was conducted to evaluate the influence of parameters such as finite element mesh density, constitutive models of recycled concrete, damage model parameters, steel-concrete friction coefficient, Poisson's ratio and modulus of elasticity of recycled concrete. Among the parameters evaluated, the most significant was the constitutive model of recycled concrete. Compared to experimental results, the numerical model properly predicted the ultimate load capacity, the Load vs. axial strain behavior of the column, and the strains in steel tube and concrete core. The validated numerical model was used to evaluate the influence of steel tube diameter (D=114.3 mm; 219.1 mm and 323.8 mm), height-diameter ratio (L/D=3, 4 and 5); diameter-thickness ratio (D/t=8.4; 18.1 and 28.6) and yield strength of steel (fy=300 MPa and 400 MPa), totaling 54 models. Regarding the ultimate load capacity, decreases were found when D/t went from 8 to 18 and from 18 to 28. There was also an increase in the ultimate load capacity when the yield stress of the steel went from 300 MPa to 400 MPa. Changing the D/t ratio from 8 to 18 was the parameter that most affected the resistant capacity of the column. Finally, there was no significant difference in the strength when the L/D ratio increased from 3 to 5. The values of ultimate load predicted using numerical modelling and Eurocode 4 (EN 1994-1-1:2004) standard procedure were very close each other. Regarding to ABNT NBR 8800 (2008) and AS/NZS 2327 (2016), both standard procedures were conservative with results about 80% of the values from numerical modelling. It is worth noting that these standards do not apply to recycled concrete.